Benjamin Franklin Bache correspondence - Bache, Benjamin Franklin, 1801-1881.
ALsS from Bache while attending Princeton University to John W. Francis regarding the American Whig Society.
U.S. Navy surgeon.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Francis, John W. -- 1789-1861 -- Correspondence; American Whig Society; Princeton University -- Societies, etc; Surgeons